Neurogenic inflammation and colliquative lymphadenitis with persistent orthopox virus DNA detection in a human case of cowpox virus infection transmitted by a domestic cat. (18th May 2015) - Hobi, S.; Mueller, R.S.; Hill, M.; Nitsche, A.; Löscher, T.; Guggemos, W.; Ständer, S.; Rjosk‐Dendorfer, D.; Wollenberg, A.
Summary: Cowpox viruses are orthopoxviruses that may survive in the environment for years. Rodents are regarded as the primary hosts, but transmission to other species has been reported. This report describes a cowpox virus infection in a cat with subsequent transmission to its owner leading to protracted, atypical and severe clinical signs. A young cat presented with multiple crusts and plaques on the neck, muzzle and tail base. The owner developed an erythematous lesion with elevated margins, central necrosis and crust formation below the left breast, a neurogenic inflammation, enlarged regional lymph nodes, a colliquative lymphadenitis and concomitant flu‐like symptoms. Cultures were taken at the first visit from the cat's lesional skin and the patient's skin, and polymerase chain reaction with sequencing of the haemagglutinin region of both were positive for cowpox virus. The patient was treated with various antibiotics and methylprednisolone and was in clinical remission after 7 months. Abstract : What's already known about this topic? Orthopoxviruses can be transmitted from animals to humans. The pathogenesis of the disease and carriers of the virus are understood. Clinical signs and treatment aspects in humans and animals have been studied. What does this study add? Severe colliquative lymphadenitis and neurogenic inflammation were observed in our case, both originating from the inoculation site. Some of the treatment aspects in this case are quite new, especially treatment with steroids.